(untitled) (Modern education and development, 2025)
Translation is more than a word-for-word conversion between two languages. It is a complex process that involves rendering meaning, tone, and cultural nuances. One of the major challenges in this process is achieving equivalence—the degree to which the translated text reflects the original in meaning and impact. This thesis examines the linguistic and cultural barriers to achieving equivalence and presents strategies that professional translators use to address these issues. Main Body